2020
DOI: 10.1111/joor.13083
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary clinical evaluation of traditional and a new digital PEEK occlusal splints for the management of sleep bruxism

Abstract: Sleep bruxism (SB) is defined previously as a kind of repetitive jaw-muscle activity mainly manifested by grinding, clenching, and/or bracing or thrusting of the mandible during sleep. 1 Although the aetiology of bruxism is not exactly clear, many studies regarded it as multiple causes including morphological, psychosocial, genetic and other possible factors. 2-5 Long-term SB can lead to tooth wear, jaw-muscle pain and occlusal trauma, and in some severe forms can cause difficulty with speech or swallowing. 6 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…Wear of occlusal devices and hard dental tissues under clinical and simulation conditions is a complicated process in comparison to other physical and mechanical properties of the materials. 24 Three studies have reported that tooth wear is analogous to bruxism [25][26][27] while two studies have contradicted this statement. 28,29 This systematic review has shown that all studies lacked standardization and precise flow.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Wear of occlusal devices and hard dental tissues under clinical and simulation conditions is a complicated process in comparison to other physical and mechanical properties of the materials. 24 Three studies have reported that tooth wear is analogous to bruxism [25][26][27] while two studies have contradicted this statement. 28,29 This systematic review has shown that all studies lacked standardization and precise flow.…”
Section: Discussionmentioning
confidence: 99%
“…32 A recent study has also confirmed the importance of polishing protocols for occlusal device materials. 33 Seven in vitro 12,[14][15][16][17][18]20 and two in vivo 24,25 studies followed polishing protocols before wear testing. Other studies 19,21 which did not follow polishing protocols had significantly greater wear after testing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations